Screening for hemoglobinopathy with capillary electrophoresis in adult patients. (28th October 2021) - Osa-Andrews, Bremansu; Desimone, Nicole; Sarode, Ravi; Paulino, Sarita; Cao, Jing
Abstract: Hemoglobinopathy screening is frequently needed in adult patients, including prenatal carrier screen, workup of unexplained anemia, and bone marrow donor and recipient screening. However, the preferred test method for screening of hemoglobinopathy is not well established due to limited guidance from professional societies. American College of Obstetricians and Gynecologists' Committee on Genetics recommended hemoglobin electrophoresis as the screening method of hemoglobinopathy in pregnancy; nevertheless, electrophoresis employs various methodologies, including acid gel electrophoresis, alkaline gel electrophoresis, and capillary electrophoresis (CE) with alkaline buffer. For other adult patient populations who need hemoglobinopathy screening, no clear guidelines dictate the method of choice. A previous study has shown that CE captures major hemoglobinopathies with comparable performance to high-performance liquid chromatography (HPLC) in pediatric patients but no study has investigated using CE alone in adult patient screening. In this retrospective study, we evaluated the utility of CE as a screening method to rule out clinically significant hemoglobin variants. During eight months, 312 adult patients without previously identified hemoglobin variants had hemoglobinopathy screening performed using a comprehensive testing algorithm. This cascade algorithm screens for hemoglobinopathy using both CE (Capillarys, Sebia, Paris, France) and HPLC (laboratory-developed test) with reflex to more advanced variant identification such as mass spectrometry and genetic analyses. Categories of abnormal findings were reviewed to determine if hemoglobinopathy can be identified by using CE only. The patient population mainly consists of pregnant women and anemic patients with hematologic malignancies with an average age of 42. Out of the 312 screened patients, 47 had abnormal results. The most frequent condition was elevated hemoglobin F (N=25) ranging 2-5% seen in leukemia patients on chemotherapy attributed to bone marrow stress. Eight cases of beta plus thalassemia (featuring hemoglobin A2 >4%) and 3 cases of hemoglobin C trait were identified in patients with little to mild clinical manifestations (red blood cell indices suggesting anemia). Decreased hemoglobin A2 fraction was observed in 7 patients, and potential causes were alpha thalassemia or iron deficiency. Other less common hemoglobinopathies included heterozygote A2 prime (N=3, a benign delta chain variant that migrates separately from hemoglobin A2 on CE) and hemoglobin G-Philadelphia (N=1). All of the abnormal results are identifiable by CE alone, although HPLC and more advanced methods help confirm the diagnosis. Our study shows that CE as the first line of screening method would rule out major hemoglobinopathies in adults. There have been reports that rare but clinically significant hemoglobin variants like hemoglobin Malmo may not be detected by CE, and therefore, certain pre-test probability factors need to be considered when testing for hemoglobinopathies, such as race/ethnicity background, family history, red blood cell indices, and iron deficiency status.